2009
DOI: 10.1002/ijc.24386
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced invasiveness of drug‐resistant acute myeloid leukemia cells through increased expression of matrix metalloproteinase‐2

Abstract: The acquired drug resistance as well as extramedullary tissue infiltration of leukemic cells is a major obstacle in leukemia treatment. Excessive egress of leukemia cell blasts results in invasion into various organs or tissues, which is facilitated by the catalytic activities of matrix metalloproteinases (MMPs). However, the migration of chemoresistant leukemia cells remains unclear. Here, we generated drug-resistant variants of the human acute myeloid leukemia cell line (AML-2/WT) by stepwise exposure to ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 29 publications
2
23
0
1
Order By: Relevance
“…This could explain the loss of heart collagen mass in doxorubicintreated animals, one of the features of anthracyclininduced cardiotoxicity. In agreement with this observation, MMP overproduction has been also described in multidrug-resistant (MDR1) tumor cells (Song et al, 2009).…”
Section: Impact Of Anti-cancer Agents On Ecm Remodelingsupporting
confidence: 63%
“…This could explain the loss of heart collagen mass in doxorubicintreated animals, one of the features of anthracyclininduced cardiotoxicity. In agreement with this observation, MMP overproduction has been also described in multidrug-resistant (MDR1) tumor cells (Song et al, 2009).…”
Section: Impact Of Anti-cancer Agents On Ecm Remodelingsupporting
confidence: 63%
“…A close association between the expression or activity of distinct matrix metalloproteinases and both tumor cell invasion and metastasis has been described [28]. Resistance of AML cells to anticancer drugs was described to be associated with increased activity and expression of MMP-2, which induced an enhancement in their invasivity [29]. This resistance of AML cells to anticancer drugs was also found to lead to a lack of drug-induced cell death, such as apoptosis.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies reported miR-21-induced chemoresistance by downregulation of PDCD4 proteins, on the basis of previous reports of the relation between PDCD4 and chemosensitivity (Jansen et al , 2004; Bourguignon et al , 2009). Moriyama et al (2009) also reported miR-21 induced chemoresistance to gemcitabine and changes in MMPs expression, and speculated that these miR-21-induced changes in chemoresistance were mediated through MMPs, based on previous reports that the miR-21 indirectly induced MMPs expression (by negative regulation of tissue inhibitor of metalloproteinases 3 (TIMP3) and reversion-inducing cysteine-rich protein with Kazal motifs (RECK)) and that MMPs levels correlated significantly with chemosensitivity (Gabriely et al , 2008; Almendro et al , 2009; Song et al , 2009). On the other hand, in addition to the confirmation of miR-21-induced chemoresistance and changes in the aforementioned target molecules in pre-miR-21-transfected cells including PTEN, PDCD4, and MMPs, we also demonstrated that the miR-21-induced changes in chemoresponse were ameliorated by downregulation of PTEN or PDCD4 by the respective siRNA.…”
Section: Discussionmentioning
confidence: 97%